Sri Lanka Development Update, June 2017 - World Bank (Washington, DC, 2017)
The Sri Lanka Development Update has two main aims. First, it reports on the key developments over the past six months in Sri Lanka’s economy, and places these in a longer term and global context. Based on these developments, and on policy changes over the period, it updates the outlook for Sri Lanka’s economy and social welfare. Second, the Update provides a more in-depth examination of selected economic and policy issues, and analysis of medium-term development challenges. It is intended for a wide audience, including policymakers, business leaders, financial market participants, and the community of analysts and professionals engaged in Sri Lanka’s evolving economy.